Iraq and the war of terror: twelve months of insurgency 2004/2005 - Rogers, Paul. (London, 2006)
Since the start of the Iraq conflict, world-renowned security expert Paul Rogers has produced a series of monthly reports scrutinizing developments in the occupation and the Iraqi response to it, drawing on the unique range of contacts and material available to the prestigious Oxford research group. Now, for the first time, Rogers has brought these reports together to provide a detailed and authoritative analysis of the last year in Iraq. Concisely-written and highly accessible, this is an indispensable book for anyone interested the middle East, us foreign policy and international security.
Keywords: Terrorism-Iraq